The Leather Industry Development in Tanggulangin in Facing Asean Economic Community (AEC) 2015 with Quantitative Strategic Planning Matrix (QSPM) - Purwoko, Bambang; Gamal, Ahmad; Kunhadi, Dedy (Archives of Business Research, 2016)
In facing the Asean Economic Community (AEC) 2015, the challenge that is being faced by Indonesian citizens of using the ASEAN market, the competitiveness is still relatively low compared other ASEANs, especially Singapore, Malaysia, and Thailand. The problem that was faced by grand entrepreneurs which incorporated in INTAKO cooperative in facing competitiveness are qualified products, SNI certificated and primary services. Then leather crafts industry in Tanggulangin, Sidoarjo needs a development strategy so that leather crafts industry in Tanggulangin could not cease to exist and is prepared to face the competitiveness. The purpose of this research is to know the leather crafts industry’s development work model which incorporated in INTAKO cooperative in facing ASEAN market especially MEA 2015’s enforcement. This development strategy is capable to compete with other/similar products from ASEAN nations. We wish that the choosing of this strategy model is capable to elevate quality products using skilled human resources, fueled raw material supplies, supporting modernized media and tools, product innovation, primary service and integrated promotion. The data analysis method that is being used was SWOT Matrix and QSPM Matrix (Quantitative Strategic Planning Matrix). The result could be concluded that the SWOT analysis to evaluated of Internal Factor and External Factor by using IFI matrix and EFE matrix and formulated into SPACE matrix that the position of the company was cuurently in an aggressive position. Meanwhile the priority being produced by QSPM Matrix is the biggest priority that is market penetration (first strategy). The result from QSPM Matrix calculation was a strategy with the highest weight as to 6,558. Data analysis method used was Matrix QSPM (Quantitative Strategic Planning Matrix). Discussion, it can be concluded that the SWOT analysis to evaluate internal and external factors by using matrix EFI and EFE and formulated into the matrix space that the position of the company is currently in an aggressive position. Based on the results of matrix calculations QSPM elected with the highest weight strategy was a first strategy (all in market penetration strategy).